Downregulation of miR-223 promotes HMGB2 expression and induces oxidative stress to activate JNK and promote autophagy in an in vitro model of acute lung injury - Hao-Yu Tan; Bei Qing; Xian-Mei Luo; Heng-Xing Liang (BMC, 2021)
Abstract Background Excessive autophagic activity in alveolar epithelial cells is one of the main causes of acute lung injury (ALI), but the underlying molecular mechanism has not been fully elucidated. Previous studies have shown that microRNAs (miRs) are involved in regulating autophagy in several diseases. This study aimed to determine the role of miR-223 in excessive autophagic activity in alveolar epithelial cells and the underlying mechanism to identify a novel therapeutic targets for the development of new drugs to treat acute respiratory distress syndrome (ARDS). Methods A549 cells were treated with lipopolysaccharide (LPS) to establish an ALI in vitro model. The expression of miR-223 and its role of miR-223 in regulating oxidative stress and autophagy in the LPS-treated A549 cells, were examined using RT-PCR, flow cytometry and ELISA. A luciferase reporter assay was performed to verify the interaction between miR-223 and the high-mobility group box 2 (HMGB2) protein. Results The results showed that the LPS treatment downregulated miR-223 expression in alveolar epithelial cells. We further proved that miR-223 directly targeted the 3-untranslated region of the HMGB2 gene and the downregulation of miR-223 increased HMGB2 protein level, which activated the JNK signalling pathway and thus induced oxidative stress and autophagy in LPS-treated alveolar epithelial cells. Knockdown of HMGB2 protein deactivated the JNK signalling pathway and inhibited autophagy and oxidative stress in alveolar epithelial cells. Conclusions The results of this study suggest that miR-223 regulates oxidative stress and autophagy in alveolar epithelial cells by targeting HMGB2 via the JNK signalling pathway.